Peran Orang Tua dalam Mencegah Perilaku LGBT di Kalangan Remaja Islam - Ainun Nisa (Tafhim Al-'Ilmi, 2021)
Abstract Teenagers are very vulnerable to news related to LGBT issues, because teenagers are a period of puberty, with very little knowledge, teenagers will easily deviate. LGBT cases in Indonesia are still very common, including in the Karawang district. Therefore, the role of parents is very important to prevent LGBT behavior. This study aims to describe the role of parents in preventing LGBT behavior among adolescents in Sirnabaya village, Telukjambe Timur sub-district, Karawang district. This study uses a descriptive qualitative approach by using data collection techniques in the form of observation, documentation, and interviews. The results of this study indicate that; The role of parents in preventing LGBT behavior among adolescents, namely; (1) Play a role in providing religious education (2) Play a role in providing sex education. This research is recommended to further researchers, so that they can conduct further research with a focus on one of the activities to prevent LGBT behavior. Keywords: Role of Parents, LGBT, Islamic Youth